2019
DOI: 10.1109/access.2019.2892509
|View full text |Cite
|
Sign up to set email alerts
|

Power Factor Control Method Based on Virtual Capacitors for Three-Phase Matrix Rectifiers

Abstract: This paper proposes a novel input power factor control method based on a concept of virtual capacitors to provide unity input power factor for three-phase matrix rectifiers. The proposed algorithm introduces, at the input terminal of the matrix rectifier, an imaginary input capacitor generated by modifying a reference vector of the space vector modulation method. The virtual input capacitor, which is fictitiously built in parallel with an input LC filter, successfully compensates for the leading power factor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Based on the research findings [28][29][30][31][32] and according to the above current-limiting starting characteristic curve, a device was developed which integrated current-limiting starting, reactive compensation, and harmonic filtering (hereinafter referred to as integrated device). The topological structure of the integrated device is shown in Figure 2.…”
Section: Topologial Structurementioning
confidence: 99%
“…Based on the research findings [28][29][30][31][32] and according to the above current-limiting starting characteristic curve, a device was developed which integrated current-limiting starting, reactive compensation, and harmonic filtering (hereinafter referred to as integrated device). The topological structure of the integrated device is shown in Figure 2.…”
Section: Topologial Structurementioning
confidence: 99%
“…Basically, it is a single-stage bidirectional current source AC-DC converter, which rectifies the sinusoidal AC signals to the pure DC signals. Different modulation strategies have been applied for the AC-DC MCs, such as the Alesina-Venturini [5], the pulse-width modulation (PWM) [10,11], the model predictive control (MPC) [12][13][14], and the space vector modulation (SVM) [15][16][17][18][19][20][21]. Predictive control strategies for the AC-DC MCs under unbalanced grid voltage were proposed in [12] and [13].…”
Section: Introductionmentioning
confidence: 99%
“…The optimized modulation strategy to deduce the charging current ripple for vehicle to grid (V2G) applications using the AC-DC MC was presented in [20]. An input power factor control method was studied in [21] based on the concept of the virtual capacitor. A controlled rectifier was implemented in [22] using the AC-AC MC theory.…”
Section: Introductionmentioning
confidence: 99%
“…Several modulation methods have been successfully adapted to the AC-DC MCs [9]. An AC-DC MC is traditionally controlled by a space vector modulation algorithm [10][11][12][13][14][15][16][17]. Literature [10] presents a digitally controlled power supply for isolated three-phase AC-DC MCs without modulation blocks.…”
Section: Introductionmentioning
confidence: 99%
“…DC current ripple reduction algorithms are studied in References [15,16]. Application of the virtual capacitor concept to the AC-DC MCs to control the input power factor is presented in Reference [17]. Recent studies have shown the massive potential of model predictive control (MPC) thanks to the advanced development of fast and powerful digital microprocessors and power devices [18,19].…”
Section: Introductionmentioning
confidence: 99%